Characterization of the micro-environment of the testis that shapes the phenotype and function of testicular macrophages - Wang, Ming; Justus Liebig University Giessen (My University, 2017)
Tissue-specific macrophages are important for the activation of innate immune responses and general organ homeostasis. Testicular macrophages (TM) reside in the testicular interstitial space and comprise the largest leukocyte population in the testis and are assumed to play a role in maintaining testicular immune privilege. Numerous studies have indicated that the interstitial fluid (IF) surrounding the TM has immunosuppressive properties, which may influence the TM phenotype. However, the identity of the immunosuppressive molecules present in the IF is poorly characterized. In this thesis it is shown that in the rat, IF shifts the M1 phenotype of granulocyte macrophage-colony stimulating factor induced bone marrow derived macrophages towards the M2 phenotype. M2 macrophages polarized by IF mimic the properties of TM such as increased expression of CD163, high secretion of IL-10 and low secretion of TNF-alpha. In addition, IF-polarized macrophages display immunoregulatory functions by inducing the expansion of immunosuppressive regulatory T cells. This thesis provides evidence that PGE2, PGI2, testosterone and corticosterone are important immunoregulatory molecules in the IF, playing a relevant role in determining the phenotype of TM. Except corticosterone, all of these factors are able to inhibit the NF-kB signaling pathway to suppress the production of pro-inflammatory cytokines and thus maintain an immunosuppressive microenvironment of the testis. Corticosterone was found to be the principal immunosuppressive molecule in the IF. Its receptor, the glucocorticoid receptor, was found to be present in TM immunohistochemically. In addition, TM locally produce small amounts of corticosterone, which suppress the expression of inflammatory genes and render TM refractory to inflammatory stimuli. Taken together, these results suggest that testicular corticosterone shapes the immunosuppressive function and phenotype of TM. This steroid hormone may therefore play also an important role in the establishment and maintenance of the immune privilege of the testis.

Gewebsspezifische Makrophagen haben eine wichtige Funktion bei der Aktivierung angeborener Immunantworten und der Organhomeostase. Testikuläre Makrophagen (TM) befinden sich im Interstitium des Hodens und stellen die größte Leukozytenpopulation in der männlichen Gonade dar. Es wird angenommen, dass sie eine wichtige Funktion in der Aufrechterhaltung des Immunprivilegs des Hodens ausüben. Studien haben gezeigt, dass die interstitielle Flüssigkeit (IF), wleche die TM umgibt, immunsuppressive Eigenschaften aufweist, die den Phänotyp der TM beeinflussen könnten. Allerdings konnten immunsuppressive Moleküle in der IF bislang kaum charakterisiert werden.In der vorliegenden Arbeit wird für die Ratte als Modell gezeigt, dass die IF den durch Granulozyten- Makrophagen-Kolonie-stimulierenden Faktor (GM-CSF) induzierten M1 Phänotyp von Makrophagen, die aus dem Knochenmark isoliert wurden, in Richtung des M2 Phänotyps verschieben kann. IF-polarisierte M2-Makrophagen zeigen damit charakteristische Eigenschaften von TM, wie z. Bsp. erhöhte Expression von CD163, hohe Level von sezerniertem IL-10 bei geringer TNF-alpha Sekretion. Darüber hinaus zeigen IF-polarisierte Makrophagen immunoregulatorische Funktionen, indem sie die Expansion von immunsuppressiven regulatorischen T-Zellen induzieren. In dieser Studie werden erstmals auch Ergebnisse vorgestellt, die zeigen, dass PGE2, PGI2, Testosteron und Corticosteron wichtige immunregulatorische Moleküle in der IF darstellen und eine wesentliche Rolle bei der Bestimmung des TM-Phänotyps spielen. Mit Ausnahme von Corticosteron sind die genannten Faktoren in der Lage, den NF-kB-Signalweg zu hemmen, und damit die Produktion von entzündungshemmenden Zytokinen zu unterdrücken. Bei Corticosteron war der NFkB Signalweg bei der Immunsuppression nicht blockiert. Corticosteron konnte als wichtigster immunsuppressiver Faktor in der IF identifiziert werden. Dessen Rezeptor, der Glucocorticoidrezeptor, konnte in TM mittels Immunhistochemie gefunden werden. TM produzieren lokal moderate Mengen an Corticosteron, die die Expression inflammatorischer Gene unterdrücken und TM unempfindlich gegenüber entzündlichen Stimuli machen können.Zusammengenommen zeigen diese Ergebnisse, dass testikuläres Corticosteron maßgeblich für die immunsuppressive Funktion und den spezifischen Phänotyp der TM verantwortlich ist. Damit könnte das Steroidhormon auch eine wichtige Rolle bei der Etablierung und Aufrechterhaltung des Immunprivilegs im Hoden spielen.
Keywords: testicular macrophages; micro-environment; phenotype; ddc:610